2020
DOI: 10.3389/fmolb.2020.604766
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of the N6-Methyladenosine RNA Methylation Regulator YTHDF1 as a Novel Prognostic Marker and Potential Target for Hepatocellular Carcinoma

Abstract: Purpose: N6-methyladenosine (m6A) RNA methylation has been implicated in various malignancies. This study aimed to identify the m6A methylation regulator-based prognostic signature for hepatocellular carcinoma (HCC) as well as provide candidate targets for HCC treatment.Methods: The least absolute shrinkage and selection operator (LASSO) analyses were performed to identify a risk signature in The Cancer Genome Atlas (TCGA) datasets. The risk signature was further validated in International Cancer Genome Consor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…Our study confirmed this promotion effect of YTHDF1 in the other two HCC cell lines Huh7 and MHCC-97H, which to a certain extent ruled out the cell dependence of YTHDF1 on this carcinogenic role of HCC. Interestingly, our study also demonstrated that YTHDF1 facilitated HCC cell cycle progression, which was predicted and indicated by previous studies [28,29,36]. The PI3K/AKT/mTOR signaling pathway plays a broad spectrum role in physiology, and its dysregulation often leads to multiple diseases, including cancer [37][38][39][40].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study confirmed this promotion effect of YTHDF1 in the other two HCC cell lines Huh7 and MHCC-97H, which to a certain extent ruled out the cell dependence of YTHDF1 on this carcinogenic role of HCC. Interestingly, our study also demonstrated that YTHDF1 facilitated HCC cell cycle progression, which was predicted and indicated by previous studies [28,29,36]. The PI3K/AKT/mTOR signaling pathway plays a broad spectrum role in physiology, and its dysregulation often leads to multiple diseases, including cancer [37][38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…The abnormal activation of this well-characterized pathway affects cell proliferation and metabolism, and leads to less tumor differentiation, poor prognosis, and earlier recurrence in HCC, but has nothing to do with the underlying etiology of HCC [43]. Based on the previous study [36], we found that the PI3K/AKT/mTOR signaling pathway might be associated with the carcinogenic role of YTHDF1 in HCC by using bioinformatic GSEA. Then, the results of western blot assay indicated that the downregulation of YTHDF1 significantly decreased the expression of key pathway proteins AKT, p-AKT, mTOR, and p-mTOR.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…YTHDF1 high expression was correlated with high pathological grade and advanced stage, which indicates YTHDF1 may be involved in the migration and metastasis of HCC. Indeed, previous studies have confirmed that upregulation of YTHDF1 improve the migratory and invasive capabilities of HCC cells ( 30 , 31 ), which provide clues for the investigation of circMAP2K4/miR-139-5p/YTHDF1 axis in the migration and metastasis of HCC in our future study.…”
Section: Discussionsupporting
confidence: 68%
“…As an m 6 A reader, YTHDF is also involved in the occurrence of HCC. YTHDF1 promotes HCC progression by enhancing FZD5 mRNA translation or AKT/GSK-3β/β-catenin signaling activation ( 30 , 31 ). YTHDF2 is involved in the decay of IL11 and Serpine2 mRNA, which are important genes that regulate the normalization and inflammation of vessels ( 32 ).…”
Section: Discussionmentioning
confidence: 99%